Studies of the Dirac Point in a GO/P3HT Nanocomposite Thin-Film Phototransistor - Yousfi, Y.; Jouili, A.; Mansouri, S.; El Mir, L.; Al-Ghamdi, Ahmed; Yakuphanoğlu, Fahrettin (Springer, 2020)
Developing a numerical model for thin-film transistors has become significant for optoelectronic applications. In this study, we describe the shift of the Dirac point in a graphene oxide thin-film phototransistor doped with various ratios of poly (3-hexylthiophene) (P3HT) (0.01 and 0.05). According the electrical characteristics of graphene oxide/poly (3-hexylthiophene) thin-film transistors and based on the proposed model, we simulate the carrier concentration, the Fermi level (E-f), the mobility (mu), and the conductivity (sigma) of charge carriers, the square resistance, and the Seebeck coefficient as a function of the applied gate voltage in the dark and under the illumination of 100 mW/cm(2), using Matlab/Simulink. The results show that, when applying a negative gate voltage, the Fermi level of graphene will shift below the Dirac point, due to the electrical field effect induced by the P3HT molar ratios and the illumination effect. This shift is exhibited more obviously in the mainly simulated parameters, and can be explained by the molar ratios of P3HT, which modulate the displacement field to allow the opening of a transport band gap through a Colombian force created by the oxygen groups. This work can provide a theoretical basis for analyzing the characteristics of these components for application in the logic circuit domain.
Keywords: GO; P3HT-TFT; Dirac point shift; conductivity; Fermi level; Seebeck coefficient